The design and development of solar kettle - Muhammad Fikhri Suhaimi (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to design and develop a solar kettle that used for outdoor activities only and also to ease to the user in getting a clean water source without hardwork. This study involved the search for information, the suitable material that can be use, the efficient rate of heat transfer and the manufacturing process of a solar kettle. This opportunity has been used to investigate a few materials that have high efficiency for rate of heat transfer and thataterial will be used as a major compnent in fabricating solar kettle. Some simulation been done using ANAYS and CATIA software to relate the suitable material for generate high efficiency of heat transfer rate